Where does the peanut smut pathogen, Thecaphora frezii, fit in the spectrum of smut diseases? - Arias, Silvina Lorena (2021)
Smut fungi, such as Ustilago maydis, have been studied extensively as a model for plant-pathogenic basidiomycetes. However, little attention has been paid to smut diseases of agronomic importance that are caused by species of the genus Thecaphora, probably due to their more localized distribution. Peanut smut incited by Thecaphora frezii has been reported only in South America, and Argentina is the only country where this disease has been noted in commercial peanut production. In this work, important advances in deciphering T. frezii specific biology/pathobiology in relation to potato (T. solani), wheat (U. tritici), and barley (U. nuda) smuts are presented. We summarize the state of knowledge of fungal effectors, functionally characterized to date in U. maydis and most recently in T. thlaspeos, as well as the potential to be present in other Thecaphora species involved in dicot-host interactions like T. frezii-peanut. We also discuss applicability and limitations of currently available methods for identification of smut fungi in different situations and management strategies to reduce their impact on agri-food quality. We conclude by describing some of the challenges in elucidating T. frezii strategies that allow it to infect the host and tolerate or evade plant immune defense mechanisms, and assessing other aspects related to pest control and their implications for human health.